Macroeconomic policy regimes and demand and growth regimes in emerging market economies: the case of Argentina - Ianni, Juan Martin (2024)
Demand and growth regimes (DGR) and macroeconomic policy regimes (MPR) frameworks have assumed prominence within the post-Keynesian literature. However, most studies based on these conceptual frameworks have focused on developed economies. The main contribution of this paper is to provide a post-Keynesian analysis of the DGR and MPR of an emerging capitalist economy, Argentina, in the period between 2002 and 2019. By providing a novel periodization of the Argentine macroeconomic development, the results show a more precise characterization of the latter, thus allowing a better understanding of economic policy and its results in terms of aggregate demand and growth. In particular, it is possible to observe the MPR and DGR transition between 2002 and 2015, as well as an abrupt change after 2016.